Genetics of diabetes and its complications: a comprehensive review - Abdul Sami; Ahsan Javed; Dilber Uzun Ozsahin; Ilker Ozsahin; Khalid Muhammad; Yasir Waheed (Diabetology & Metabolic Syndrome)
Abstract Background Diabetes mellitus (DM) affects hundreds of millions of people worldwide. Genetic research plays a crucial role in managing diabetes by providing valuable insights into genetic predispositions, facilitating early diagnosis, and enabling personalized treatment strategies. Identification of important genetic markers has paved the way for the creation of targeted therapies, enhancing treatment outcomes and promoting preventive care for both type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM). The aim of this study is to explore the role of different genes in the development of DM and its related complications. Methodology A comprehensive literature search was conducted from October 27 to November 14, 2024, to enlist articles related to genes involved in development of DM and its complications in search engines including PubMed, Medline, Google Scholar, and Scopus. We included original articles, case–control studies, cohort studies, review articles, systematic review, and meta-analysis published between January 1, 2014, and November 14, 2024 in our study. Results In T1DM; research has historically concentrated on the role of HLA class II genes. However, recent studies have brought attention to the role of HLA class I genes in the disease’s development, suggesting a broader role of genetics than previously understood. CTLA4, IL2RA, and PTPN22, genes were also significantly linked to T1DM. In T2DM; TCF7L2 was found to be the most potent gene for its development among others genes such as LCAT, APOE, FTO. For gestational diabetes mellitus (GDM), MTNR1B, CDKAL1, and IRS1 genes played an important role. Conclusion Genetics played an important role in the understanding of DM. Researchers have identified new genetic loci that can serve as diagnostic markers for DM and its associated compilations such as diabetic kidney disease (DKD), diabetic neuropathy (DN), diabetic retinopathy (DR) and cardiovascular diseases (CVDs). TCF7L2 and HLA class II are the strongest risk factors for T2DM and T1DM, respectively. Understanding the genetics of DM and its complications is essential for improving early detection, enhancing treatment outcomes, and developing targeted therapies for DM patients.